Different types of chillies used to make the base - Mumbai Archive Project Team (Jio Institute, 2024)
Each family uses different types of chillies to make the base. Kashmiri chillies are a staple in many dishes because of their deep red hue and ability to temper the heat without overpowering the dish. Other pungent chillies, including Resham Patti, Bedki, Bird’s Eye, and Sankeshwari, can also be used to make the base.